Tingkat Akurasi dalam Analisis Perbandingan Metode ORESTE dengan PSI terhadap Penilai Kinerja Dosen - Hamjah Arahman (Jurnal Informasi dan Teknologi, 2023)
Technology that is increasingly easy to use has been embedded in all aspects of life, appraisal system technology is one of many intelligent systems that facilitate human work in the level of accuracy of performance appraisal. The quality of the lecturer's performance is not good and quality, resulting in the reduced quality of lecturer dedication and the quality of students at STMIK Triguna Dharma Medan. Therefore, a method is needed to identify the causes of the optimal and effective assessment of lecturer performance to facilitate improving the quality of lecturers and students at STMIK Triguna Dharma Medan. Researchers use comparisons to find out which system is more effective and accurate in determining lecturer performance appraisal using DSS (Decision Support System). This decision support system is to determine the best criteria in determining the best value weights from a comparison of two methods, namely the ORESTE method with PSI (Preference selection index) in solving the material and determining the best level of accuracy of performance assessment in this case, where the ORESTE method uses the Besson process. rank which means this method uses ranking and ordinal data. The PSI (Preference Selection Index) method was chosen because it can determine the weight value for each attribute, in this case it can be continued with ranking which will be able to select each attribute from the best alternative from several existing alternatives, so that the results are obtained from the selection of the best weight. , namely the best lecturer performance